Enhancing aviation security awareness of vocational students from travel agent major of SMK Sriwijaya, Palembang - Pinem, Yune Andryani; Jumlad , Walid; Frisnawati, Elnia; Andarini , Siska Ayu (Jurnal Pemberdayaan: Publikasi Hasil Pengabdian Kepada Masyarakat, 2023)
Playing a crucial role in ensuring an aviation operation's safety and security, an Aviation Security Officer (AVSEC) is equipped with particular knowledge and skills. These are regulated in an international standard and ministered by the Directorate General of Civil Aviation (DGCA) as an Indonesian administrator. To apply as an AVSEC, the compulsory administrative requirement is an AVSEC license issued by DGCA. Special training and competency tests are held by approved institutions at cost. Minimizing the cost while providing adequate training for its students, Sriwijaya Aviation Vocational School decided to participate in a community service program held by STTKD, School of Aerospace Technology. The program specifically complies with knowledge provision and skills practice around AVSEC duties. Materials are designed as close as possible to approved AVSEC training and tests to help participants with the provision to take the real test. Among all the material in an approved AVSEC training, this program delivers material about AVSEC duties and problems, situational awareness at the airport, and politeness in English imperative for AVSEC.